2002
DOI: 10.1152/ajpheart.00739.2001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term inhibition of nitric oxide synthesis increases arterial thrombogenecity in rat carotid artery

Abstract: Kubo-Inoue, Mayuko, Kensuke Egashira, Makoto Usui, Masao Takemoto, Kisho Ohtani, Makoto Katoh, Hiroaki Shimokawa, and Akira Takeshita. Long-term inhibition of nitric oxide synthesis increases arterial thrombogenecity in rat carotid artery. Am J Physiol Heart Circ Physiol 282: H1478-H1484, 2002. First published November 29, 2001 10.1152/ajpheart.00739.2001.-Reduced activity of endothelial nitric oxide (NO) may be involved in thrombus formation on atherosclerotic plaques, a major cause of acute coronary syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…PAI-1 and tissue factor are prothrombotic molecules that are modulated by redox stimuli. [27][28][29][30][31] Tissue factor activates thrombin, and elevated tissue factor expression is associated with thrombosis in atherosclerosis and sepsis. 32,33 Tissue factor expression is inhibited tissue factor endothelial NO ⅐ production.…”
Section: Our Data Indicate That the Increase In Omentioning
confidence: 99%
“…PAI-1 and tissue factor are prothrombotic molecules that are modulated by redox stimuli. [27][28][29][30][31] Tissue factor activates thrombin, and elevated tissue factor expression is associated with thrombosis in atherosclerosis and sepsis. 32,33 Tissue factor expression is inhibited tissue factor endothelial NO ⅐ production.…”
Section: Our Data Indicate That the Increase In Omentioning
confidence: 99%
“…The fourth group (L + Hyd group) ( n = 10) received L-NAME and hydralazine (L-NAME: 0.7 mg/ml; hydralazine: 0.2 mg/ml; Nacalai Tesque Co.) in its drinking water. These doses of imidapril and hydralazine were chosen based on their previously reported ability to normalize the L-NAME-induced increase in systolic blood pressure (SBP) ( 11 ).…”
Section: Animals Experimental Protocolmentioning
confidence: 99%
“…2 Using the same model of long-term inhibition of NO increased arterial thrombogenicity along with upregulated expression of TF. 8 Our study may thus provide a possible mechanism involving MCP-1/CCR2-mediated Ca 2ϩ influx for the increased TF expression in the monocyte-EC interaction in their animal model in vivo. The present study suggests the role of MCP-1/CCR2 in procoagulant activity in the vascular wall, which is critical for the development of early atherosclerosis and the formation of vulnerable plaques.…”
Section: Discussionmentioning
confidence: 74%
“…7 In vivo studies with a rat model showed that inhibition of NO synthesis by L-NAME increased MCP-1 expression and induced increased arterial thrombogenicity including upregulated expression of TF and the resultant thrombin generation. 2,8 Intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) consists of intracellular mobilization from Ca 2ϩ stores and influx via the plasma membrane. The upregulated expression of TF is inhibited by 1,2-bis(o-amino-5-fluorophenoxy)ethane-N,N,Nc,Nc-tetraacetic acid tetraacetoxymethylester (BAPTA-AM) chelation of Ca 2ϩ in cultured smooth muscle cells, indicating that Ca 2ϩ signaling is involved in the induction of TF gene expression.…”
Section: Conclusion-mcp-1/ccr2 May Play a Role Inmentioning
confidence: 99%